DETERMINE THE COEFFICIENT OF STATIC WIND ON BRIDGE STRUCTURE (Jurnal Teknologi (Sciences & Engineering), 2016)
A bridge structure should have a resistance to wind loads. The purpose of research is determine the coefficient of static wind load using computational calculations with FLUENT. The objects were modeled into a square 1x1 m, rectangle 2x1 m and circle diameter of 1 m with velocity of wind 10 m/s, 20 m/s and 30 m/s. The results described the value of the coefficient of drag force (CD) for square shape larger than rectangle. The coefficient of drag force (CD) for rectangular shape larger than circle. The value of coefficient of static wind do not depend on dimensional and wind speed. The coefficient value of wind static for Suramadu bridge which calculated by FLUENT Program and wind tunnel test have a similar chart patterns.